An experimental study of the effects of combined exposure to microwave and heat on gene expression and sperm parameters in mice - Faezeh A Gohari; Behzad Saranjam; Mohsen Asgari; Leila Omidi; Hamid Ekrami; Seyyed Ali Moussavi-Najarkola (Wolters Kluwer Medknow Publications, 2017)
Objectives: Separate exposure to microwaves (MWs) or heat had effects on expression levels of Bax and Bcl-2 and sperm parameters in studied group. Aims: The objectives of this research were to determine the effects of separate and combined exposure to 900-MHz MW (as representative of cell phone radiation) and heat on gene expression and spermogram of male mice. Settings and Design: This experimental animal study was conducted in the school of public health. Materials and Methods: The study was done on 12 male mice randomly divided into four groups (21-23 g): control, test group 1 with separate exposure to 900-MHz MW, test group 2 with separate exposure to hot and sultry climate, and test group 3 with simultaneous whole body exposures to 900-MHz MW and hot and sultry climate. In all studied groups, gene expression and sperm parameters were measured. Results: Tissue samples in all test groups showed integrity of the seminiferous tubule followed by all types of germ line cells. Significant increases in the number of dead sperms in mice with separate exposure to heat were observed in comparison with the other studied groups (P < 0.05). The ratio of Bax expression was elevated to 0.015 ± 0.006 in mice after combined exposures to 900-MHz MW and heat. Conclusion: Separate and combined exposure to 900-MHz MW and heat may induce adverse effects on sperm parameters and gene expression of studied male mice.